TRANSFORMATIONS IN THE SYSTEM OF SCIENTIFIC COMMUNICATIONS IN THE INFORMATION SOCIETY - Скиба, O. П (Proceedings of the National Aviation University Series Philosophy Cultural, 2019)
Introduction. The article is devoted to the study of the features of functioning of the latest information and communication systems in the Information age. The aim and tasks. The emergence of electronic virtual reality, significantly changes the form of relationship between people, so the study of the socio-cultural aspect of information and communication systems is necessary. Since innovative forms of communication still play a significant role in scientific activity and information exchange, it is necessary to pay attention to the study of the features of functioning of the newest systems of scientific communications. Research methods. Theoretical and methodological basis of the research are general scientific and special methods and approaches enable the author to study the changes in the scientific communications system in conditions of the Information society. One such approach is a system approach, supplemented by synergy. Research results. When the latest information and communication technologies provide the information exchange, the task of detecting and tracing all the contacts of a group of people forming the majority of the research team is further complicated. Moreover, to solve radically new problems of modern science, groups of scientists are formed from different continents rather then from different countries. At the same time, their communication is not always direct: every scientist can solve a single task, engaging in social networking. But complex, global scientific problems are solved by teams of scientists that are directly related and work side by side, as in the case of studying the phenomenon of the Big Bang with the help of the android collider. Discussion. Thus, in the Information age, as we see, the ability of a person to communicate, his value orientations, personal skills and abilities to use the existing information and communication technologies depend on the outcome of the decision of the scientific problem and on the professional career as well as leisure. Conclusion. In the conditions of the development of modern civilization new forms of communication act as an important tool of social transformations emerged. Virtual communications form their own socio-cultural space, radically change the process of scientific knowledge and methodology of scientific research